Survey of Physical Activity of Students of SMPN 2 Tarik Sidoarjo During the Pandemic Covid-19 - YULINAR AININ NUR SA'ADA; DONY ANDRIJIANTO (Universitas Pendidikan Indonesia (UPI), 2022)
Introduction: Covid-19 in the world continues to mutate and form a new variant, namely the Omicron variant, so that community activities are limited so that healthy life behaviors are constantly maintained, starting from wearing masks, washing hands, and not allowing direct contact with the family to friends. Purpose: This study was intended to determine the physical activity of 9th-grade students of SMPN 2 Tarik during the pandemic. Methods: Applying a quantitative descriptive approach with a survey method. The total population used is 249, with a sample of 156 respondents. The sampling technique used is simple random sampling. The instrument used is a Questionnaire Physical Activity Questionnaire for Adolescents, which adopts from previous research that has been tested for validity with a value of -0.010 - 0.0506 and reliability of 0.682 - 0.745 so that it is declared valid and reliable, used to measure physical strength activity according to by age and distributed via Google Form with data analysis techniques assisted by Microsoft Excel. Â Results: From the data results, the biological activity of students was 42.3%, with a total of 66 students in the low category. Then 45.5% in the medium category as many as 71 students, and for the last one, the percentage of 12.2% is included in the high sort with 19 students. Conclusions: It can be concluded that all student activities during the pandemic are in the moderate category, so that learning must be further improved so that students are more physically active when learning using the online system.